Development Of The Lakip Information System Using The Waterfall Method - Muhammad Yassir; Gafur; Ita Fitriati (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2024)
LAKIP becomes an important tool for evaluation and feedback for all government stakeholders. In fact, the preparation of lakip is still done manually and has not been integrated with the SKPD. The research is aimed at building a system of information preparation LAKIP in the government of the district of Polewali Mandar. The methods used are waterfall with Unified Modeling Language, Macromedia Dreamweaver CS 6 for interface design, and postgresql for database design. After a black box test, the resulting system can work in detail with precision and accuracy